Using Classroom Response Systems to Engage High School Students in Saudi Arabian Classrooms - Abu Hussain, Wedian T. (Arab Journal for Sciences and Research Publishing, 2016)
Classroom Response Systems are personal response devices that allow teachers to poll a group of students. As the use of technology, including tablets, iPads, and clicker systems, is introduced into Saudi Arabian classrooms, teachers will need to be trained in all the possible uses for the tablets and iPads that will be given to the students. Classroom Response Systems are a natural outgrowth of the type of uses teachers will need to integrate into their now-technological classrooms. The current study looks at the literature on classroom response systems and offers reasoning for the professional development of Saudi teachers in the use of classroom response systems for feedback and discussion in the science classroom. The target audience for this study are the professional development trainers of Saudi Arabian teachers, particularly teachers of high school Biology. Science curriculum has recently been changed in Saudi Arabia, and teachers are searching for ways to coordinate the curriculum with the new classroom technology that has also been recently introduced. Professional development will need to be developed to train teachers in the utilization of the new technology. Training in classroom response systems will be one part of that training. The study includes a link to an author-created training website, which includes videos of examples of classroom response systems in the classroom, interviews with students, sample tests, and guidelines for the purchase of classroom response systems.
Keywords: classroom response systems; high school; Saudi Arabia; students; classrooms